Energy Aware Load-Balancing of Parallel Mining of Frequent Sequences Using LB Scheme - Uthaman, V (International Journal of Computer Sciences and Engineering, 2025)
Data aggregation in wireless sensor networks is utilized to decrease the correspondence overhead and draw out the system lifetime. In any case, an enemy may bargain some sensor hubs, and utilize them to fashion false esteems as the aggregation result. Past secure data aggregation plans have handled this issue from various edges. The objective of those calculations is to guarantee that the Base Station (BS) does not acknowledge any fashioned aggregation comes about. However, none of them have attempted to identify the hubs that infuse into the system fake aggregation comes about. Additionally, a large portion of them for the most part have a correspondence overhead that is, (best case scenario) logarithmic per hub. In this theory, they propose a safe and vitality proficient data aggregation conspire that can recognize the malevolent hubs with a consistent per hub correspondence overhead. In our answer, all aggregation comes about are marked with the private keys of the aggregators so they can't be changed by others. Hubs on each connection also utilize their Level Based shared key for secure correspondences. Every hub gets the aggregation comes about because of its parent (sent by the parent of its parent) and its kin (by means of its parent hub), and checks the aggregation consequence of the parent hub. Hypothetical investigation on Security, vitality utilization and correspondence overhead accords with our examination based recreation contemplate over arbitrary data aggregation trees.